Factors associated with recidivism among adolescents girls in conflict with the law in an institution in Brasília, Federal District, Brazil - Andrea Donatti Gallassi; Samantha Lima dos Santos; Vagner dos Santos; Eduardo Yoshio Nakano; Benedikt Fischer; Ana Lúcia Galinkin; Gabriela Arantes Wagner (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract Recidivism is a challenge for the Brazilian socio-educational system because it is associated with personal, social and environmental factors, especially among juvenile offenders. This study examined key characteristics and potential association with recidivism in 391 female adolescent offenders from a correctional institution in Brasília, Federal District, Brazil, between 2004 and 2011. Cross-sectional data on socio-demographics, drug use and offense characteristics from institutional information were examined. Associate factors with recidivism were examined using negative binomial regression analyses. 32.5% of offenders were recidivists at present admission and the mean frequency of recidivism among recidivists was 2.16. About half (53.6%) of the sample reported drug use. After the adjustment, recidivism was positively associated with: age; offender's drug use; residence status; offense type; and no family drug use. Factors associated with juvenile offenders' recidivism confirm findings from elsewhere, and should inform targeted interventions in Brazil.